Outward Foreign Direct Investment, Exporting and Firm-Level Performance in Sub-Saharan Africa - Neil Foster-McGregor; Anders Isaksson; Florian Kaulich (The Vienna Institute for International Economic Studies (wiiw), 2013)
This paper adds to the small but growing literature that considers a relationship between the way a firm serves foreign markets and its subsequent performance. The current paper is the first to consider this issue for a sample of sub-Saharan African countries and includes data on both manufacturing and services firms. Results from a number of parametric and non-parametric tests for manufacturing industries indicate that there is a clear productivity ordering with firms undertaking outward FDI performing best, followed by exporters with domestically oriented firms performing least well. The results for services firms are more nuanced and indicate that while exporters and firms undertaking outward FDI are more productive than domestically oriented firms, there is no significant difference in productivity between these two types of firms. Despite this, average productivity and point estimates from the regression analysis on services firms suggest that the productivity of exporting firms is larger than that for firms undertaking outward FDI.
Keywords: F14; F21; 330; exports; foreign direct investment; productivity; services firms